Postbiotics: emerging therapeutic approach in diabetic retinopathy - Chen, Qin; Li, Xue-Jian; Xie, Wei; Su, Zhao-An; Qin, Guang-Ming; Yu, Chen-Huan (Frontiers in Microbiology, 2024)
Diabetic retinopathy (DR) is a prevalent microvascular complication in diabetic patients that poses a serious risk as it can cause substantial visual impairment and even vision loss. Due to the prolonged onset of DR, lengthy treatment duration, and limited therapeutic effectiveness, it is extremely important to find a new strategy for the treatment of DR. Postbiotic is an emerging dietary supplement which consists of the inactivate microbiota and its metabolites. Numerous animal experiments have demonstrated that intervention with postbiotics reduces hyperglycemia, attenuates retinal peripapillary and endothelial cell damage, improves retinal microcirculatory dysfunction, and consequently delays the progression of DR. More strikingly, unlike conventional probiotics and prebiotics, postbiotics with small molecules can directly colonize the intestinal epithelial cells, and exert heat-resistant, acid-resistant, and durable for storage. Despite few clinical significance, oral administration with postbiotics might become the effective management for the prevention and treatment of DR. In this review, we summarized the basic conception, classification, molecular mechanisms, and the advances in the therapeutic implications of postbiotics in the pathogenesis of DR. Postbiotics present great potential as a viable adjunctive therapy for DR.